A systematic review of evidence for and against routine surveillance imaging after completing treatment for childhood extracranial solid tumors. (19th May 2020) - Morgan, Jessica E.; Walker, Ruth; Harden, Melissa; Phillips, Robert S.
Abstract: Background: Regular off‐treatment imaging is often used to assess for recurrence of disease after childhood cancer treatment. It is unclear if this increases survival, or what burden surveillance places on patients, families, or health‐care services. This systematic review examines the impact of routine surveillance imaging after treatment of pediatric extracranial solid tumors. Methods: Collaborative patient and public involvement informed the design and interpretation of this work. Thirteen electronic databases, conference proceedings, and trial registries were searched alongside reference list checking and forward citation searching from 1990 onwards. Studies were screened and data were extracted by two researchers. Risk of bias was assessed using a modified ROBINS‐I tool. Relevant outcomes were overall survival, psychological distress indicators, number of imaging tests, cost‐effectiveness, and qualitative data regarding experiences of surveillance programs. PROSPERO (CRD42018103764). Results: Of 17 727 records identified, 55 studies of 10 207 patients were included. All studies used observational methods. Risk of bias for all except one study was moderate, serious, or critical. Data were too few to conduct meta‐analysis; however, narrative synthesis was performed. Surveillance strategies varied, and poorly reported, involving many scans and substantial radiation exposure (eg, neuroblastoma, median 133.5 mSv). For most diseases, surveillance imaging was not associated with increased overall survival, with the probable exception of Wilms tumor. No qualitative or psychological distress data were identified. Conclusions: At present, there is insufficient evidence to evaluate the effects of routine surveillance imaging on survival in most pediatric extracranial solid tumors. More high‐quality data are required, preferably through randomized controlled trials with well‐conducted qualitative elements. Abstract : This systematic review examines the impact of routine surveillance imaging after treatment of pediatric extracranial solid tumors on overall survival, psychological distress indicators, number of imaging tests, cost‐effectiveness, and qualitative data regarding experiences of surveillance programs. At present, there is insufficient evidence to evaluate the effects of routine surveillance imaging on survival in most pediatric extracranial solid tumors.